Combined root‐MUSIC algorithms for multi‐carrier MIMO radar with sparse uniform linear arrays. Issue 1 (1st January 2019) - Liu, Aihua; Zhang, Xin; Yang, Qiang; Wu, XiaoChuan; Deng, Weibo
Abstract : In this study, sparse uniform linear arrays are used to improve the direction‐of‐arrival (DOA) estimation accuracy for the multiple‐input multiple‐output radar. With a suitable choice of multi‐carrier frequencies, the DOA estimation ambiguity problem caused by spatial under‐sampling can be resolved. Two kinds of search‐free DOA estimation algorithms based on root‐multiple signal classification (MUSIC) are proposed. The first algorithm directly applies the root‐MUSIC to each carrier frequency separately for the true DOAs as well as their spurious DOAs, then, a novel DOA replicas matching algorithm is proposed to obtain the true DOAs from the ambiguous ones. The second algorithm utilises the manifold separation technique (MST) to align the noise subspaces of all multi‐carrier frequencies. Using the MST, the separable representation of the array manifold vector of each carrier frequency is obtained, then the root‐MUSIC polynomials of all multi‐carrier frequencies are combined to construct a new polynomial, the true DOAs can be obtained directly by applying polynomial rooting without any matching processing. The two proposed algorithms are both practical, computationally efficient and robust. Numerical simulations verify the effectiveness of the proposed algorithms in terms of root‐mean‐squared error.